Social influence and forest habitat conservation: Experimental evidence from Vermont's maple producers. Issue 9 (25th July 2019) - Byerly, Hilary; D'Amato, Anthony W.; Hagenbuch, Steve; Fisher, Brendan
Abstract: Working landscapes can provide biodiversity and ecosystem services. Many voluntary conservation programs ask those who manage working lands—farmers, ranchers, and forest landowners—to steward their resources in ways that maintain or increase these benefits. While research on landowners suggests the importance of social influence in management decisions, few studies have tested whether providing information about the behavior and opinions of others affects decisions related to private land and forest management, stewardship, or conservation. Using a randomized controlled trial design, we mailed three versions of a solicitation letter for a bird habitat conservation program to 967 individuals who manage forests to produce maple syrup. Maple producers who were messaged about recognition for participation were as likely to ask for more information about the program as those who received only a control message that described the program. Providing information about the participation of others had a negative effect on the number of producers requesting information compared to the control. These results highlight the importance of context in using social influence to change land manager behavior. Findings are relevant to conservation researchers and practitioners, offering applications of behavioral science to improve biodiversity and ecosystem service outcomes on private lands.